Answers

2014-11-08T10:03:45+05:30
Let paul's current age be x and age of Alice be y
After 2 years, paul is x+2 and alex is y+2
x+2 = 3(y+2)
x+2 = 3y +6
x = 3y + 4 ..............1
now,
x=6y
3y + 4=6y
y= 4/3

therefore age of paul is 6y which is (4/3)*6 =8years 
0
in last line there should be 6 not 4
thank u..
welcome
2014-11-08T10:17:38+05:30
Let the age of alice be x
After two yrs,paul's age + 2=3(x+2)........(i)
at present , Paul' age=6x....(ii)

from (i) and (ii)
6x+2=3(x+2)
⇒6x+2=3x+6
⇒3x=4
⇒x=4/3
Alice age=4/3 yrs 

So paul's present age=6*4/3=8 yrs.


0